PONDOK PESANTREN SALAFIYAH DAN PENUNTASAN WMIB BELMAR - Wahid Khozin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2005)
This article is an abstract of the research done by Center for Research and Development of Religious Education at ten Salafiyah Boarding School(PPS) that administer compuhaq basic education. The research is done through astudy case method so that all ten boarding schools constitute a collection of data and information used by the resexrcher tofind out their strengths and weaknesses. This collection of data is then reviewed by using CIPP pattern (Context, Input, Process, Product) introduced by Stuffle beam. The model its self, according to AbdulhamidÂ and Supriyadi, is an evaluation which is oriented more to the course of the program. This kind of evaluation is meant to give feed back to the administrators in case there are any weaknesses found in the program.